Diminishing marginal cost-effectiveness in risk-targeted lung cancer screening - Yang, Szu-Chun; Wang, Jung-Der (Translational Cancer Research, 2018)
The article, entitled “Risk-Targeted Lung Cancer Screening: A Cost-Effectiveness Analysis,” published in the Annals of Internal Medicine (1), is the first to report that the marginal gain in cost-effectiveness would be modest using risk-targeted lung cancer screening.